A Cross-cultural Comparison of Perceptions Regarding Human Trafficking (Global Journal of Human-Social Science, 2019)
This study surveyed 135 individuals of which 68 were native speakers of English and 67 were native speakers of Thai Respondents answered questions on issues related to human trafficking its causes and potential solutions Statistical tests showed significant variance in opinions between language and other groups regarding factors associated with trafficking and regarding the potential impacts of legalization of prostitution Thai responses reflected collectivist cultural perceptions while English responses reflected more individualistic views Males and English speakers were most likely to think legalized prostitution would lead to a reduction in human trafficking while females and Thais were most likely to believe legalized prostitution would increase trafficking Responses to an open-ended question showed participants felt similarly about potential remedies for human trafficking including information and awareness campaigns interaction between civilians and police increased penalties for offenders and reduction in macro-environmental variables such as poverty